hi
solve this_______€I will Mark u brainlist
Attachments:
![](https://hi-static.z-dn.net/files/db0/739bcdbf7ef4a0f8eb3dad5dedfa636b.jpg)
Anonymous:
3 c^2 - 3c - 14 c + 14 = 3 c( c-1) - 14 ( c - 1 ) = ( 3c - 14) ( c - 1)
Answers
Answered by
2
hello mate!............
given........
![3c {}^{2} - 17c + 14 = 0 \\ \\ 3c {}^{2} - 14c - 3c + 14 = 0 \\ \\ 3c {}^{2} - 3c - 14c + 14 = 0 \\ \\ 3c(c - 1) - 14(c - 1) = 0 \\ \\ (c - 1)(3c - 14) = 0 \\ \\ c = 1 \: an d \: \frac{14}{3} 3c {}^{2} - 17c + 14 = 0 \\ \\ 3c {}^{2} - 14c - 3c + 14 = 0 \\ \\ 3c {}^{2} - 3c - 14c + 14 = 0 \\ \\ 3c(c - 1) - 14(c - 1) = 0 \\ \\ (c - 1)(3c - 14) = 0 \\ \\ c = 1 \: an d \: \frac{14}{3}](https://tex.z-dn.net/?f=3c+%7B%7D%5E%7B2%7D++-+17c+%2B+14+%3D+0+%5C%5C++%5C%5C+3c+%7B%7D%5E%7B2%7D++-+14c+-+3c+%2B+14+%3D+0+%5C%5C++%5C%5C+3c+%7B%7D%5E%7B2%7D++-+3c+-+14c+%2B+14+%3D+0+%5C%5C++%5C%5C+3c%28c+-+1%29+-+14%28c+-+1%29+%3D+0+%5C%5C++%5C%5C+%28c+-+1%29%283c+-+14%29+%3D+0+%5C%5C++%5C%5C+c+%3D+1+%5C%3A+an+d+%5C%3A++%5Cfrac%7B14%7D%7B3%7D+)
hope it helps u dear......
given........
hope it helps u dear......
Answered by
1
I think it helps you dear
Mark brain liest
and follow me
Mark brain liest
and follow me
Attachments:
![](https://hi-static.z-dn.net/files/d98/e74969a1b8583846c37e609d226b942b.jpg)
Similar questions
CBSE BOARD XII,
8 months ago
English,
8 months ago
Math,
1 year ago
Math,
1 year ago
Social Sciences,
1 year ago